HUBUNGAN PEMAKAIAN KONTRASEPSI HORMONAL DENGAN KEJADIAN KANKER PAYUDARA - Umi Mustikasari; Sriwidya Astuti Khati (Jurnal Kesehatan Tambusai, 2022)
Breast Cancer is a malignant tumor in the breast or one breast. Based on the data obtained at the Arifin Achmad Regional General Hospital in 2017, the number of breast cancer patients was 2,217 cases and until now it is still ranked first in the 10 biggest diseases in the Arifin Achmad Province Riau Hospital. The purpose of this study is to know the relationship between hormonal contraception and the incidence of cancer in polyclinics and inpatient care at Arifin Achmad Hospital in 2018. The design of this study was case control with a sample of 194 cases and 194 controls. Data were collected in the form of secondary data. Random sample technique Systematic Random Sampling. Data were analyzed bivariate by Chi-Square and multivariate by using Double Logistic Regression test risk factor model. The results of the research showed that there was a relationship between the use of hormonal contraception and the incidence of breast cancer (p-value = 0,000) with OR = 3,824. The conclusion is that women who use hormonal contraception are 3 times more likely to develop breast cancer than women who do not breast cancer. In addition, the risk of using hormonal contraception is controlled by family history, parity, and breastfeeding.